2017
DOI: 10.1080/09638237.2017.1322184
|View full text |Cite
|
Sign up to set email alerts
|

Exploring experiences of and attitudes towards mental illness and disclosure amongst health care professionals: a qualitative study

Abstract: Background: The literature suggests that many health professionals hold stigmatising attitudes towards those with mental illness and that this impacts on patient care. Little attention has been given to how these attitudes affect colleagues with a mental illness. Current research demonstrates that stigma and discrimination are common in the UK workplace and impact on one's decision to disclose mental illness. Aims: This study aims to explore health professionals' experiences of and attitudes towards mental ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 37 publications
4
57
0
2
Order By: Relevance
“…Indeed, similar results were found in the United Kingdom, another country with a masculine culture (11th of 76 countries; Hofstede et al., ). Fear of negative perceptions toward mental health problems in a workplace also was reported among U.K. workers (Kotera, Adhikari, et al., ; Waugh, Lethem, Sherring, & Henderson, ). Future research should explore how these cultural dimensions and factors are related to mental health attitudes in people from different cultures and countries.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, similar results were found in the United Kingdom, another country with a masculine culture (11th of 76 countries; Hofstede et al., ). Fear of negative perceptions toward mental health problems in a workplace also was reported among U.K. workers (Kotera, Adhikari, et al., ; Waugh, Lethem, Sherring, & Henderson, ). Future research should explore how these cultural dimensions and factors are related to mental health attitudes in people from different cultures and countries.…”
Section: Discussionmentioning
confidence: 83%
“…Qualitative findings also suggested that health visitors drew on their personal experience of mental illness to support mothers; although primarily with mothers who had postnatal depression. Others have also found that professionals, including health visitors draw on their personal experiences of mental illness to help them empathize with and respond to mothers (Oates, Drey, & Jones, ; Waugh, Lethem, Sherring, & Henderson, ). As expertise by experience has become an increasingly valued element of service design and delivery professionals are increasingly encouraged to reflect on their own personal experiences and challenges of managing mental ill health to empathize with and to better engage service users (Oates et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from the preceding accounts that police culture inhibits emotional expression, often perpetuating the stigma associated with help-seeking for psychological distress (Tuckey et al 2012), or for fear of stigma and discrimination from colleagues (Waugh et al 2017).…”
Section: Subtheme 12: Emotional Response Is a Sign Of Weaknessmentioning
confidence: 99%